An Integrated Design Approach for Complex Fixed Dental Prosthesis - Budiono; Murti Indrastuti; Sri Budi Barunawati; Titik Ismiyati (Jurnal Kesehatan Gigi, 2026)
ABSTRACT Background: Replacing two adjacent anterior teeth, especially canines, poses significant biomechanical and esthetic challenges. The canine region plays a critical role in occlusal guidance and receives substantial lateral forces, making the design of fixed dental prostheses (FDPs) in this area inherently complex. Anterior esthetic demands, occlusal function, and connector integrity must be carefully integrated into the prosthetic plan. Objective: This case report aims to demonstrate an integrated prosthodontic design approach for a complex fiveunit zirconia FDP replacing maxillary teeth 22 and 23, focusing on biomechanical stability, esthetic proportion, and material selection. Case Report: A 39-year-old female presented with missing teeth 22 and 23. A five-unit FDP with two pontics and three abutments (teeth 11, 21, and 24) was planned using monolithic 4Y-TZP zirconia. The abutment selection followed Ante’s Law, and the connector was designed with an oval crosssectional area of 13 mm² to accommodate increased functional stress. A modified ridge-lap pontic was selected for esthetics and hygiene access. Surface treatment before cementation included airborne particle abrasion, cleaning with NaOH-based agent, and application of 10-MDP primer prior to dual-cure resin cementation. One-week follow-up showed excellent soft tissue response, stable occlusion, and high patient satisfaction. Conclusion: Restoration of adjacent canines using 4Y-TZP zirconia FDP demands precise design strategies. This case illustrates how an integrated approach ensures biomechanical reliability, esthetic outcome, and long-term success in complex anterior prosthetic rehabilitation. Keyword: Complex Fixed; Dental Prosthesis; Canine Replacement; 4Y-TZP Zirconia; Connector Design; Anterior Esthetic ZONE